PENCEGAHAAN PENCEMARAN AIR SUNGAI CITARUM AKIBAT LIMBAH INDUSTRI - Setiady, Tri (Yustitia, 2017)
Law Number 32 of 2009 concerning Environmental Protection and Management aims to protect or prevent and overcome environmental pollution and / or damage caused by industrial processes in which this sector often pollutes and / or damages the environment and loss to the community. Domestic waste as a contributor to the biggest yeng river pollution is waste generation. This causes the river flow to be hampered and cause flooding. While the biggest contributor to river pollution in terms of industrial waste is the disposal of hazardous and toxic wastes that go directly to the river without any prior processing.